Flume Experiment Evaluation of Resistivity Probes as a New Tool for Monitoring Gas Migration in Multilayered Sediments. (December 2020) - Wu, Jingxin; Guo, Xiujun; Sun, Xiang; Sun, Hao
Highlights: Ring-electrode resistivity probes can effectively monitor various gas migration processes. Ring-electrode resistivity probes can effectively monitor the direction, rate, and range of gas migration. Circular point-electrode resistivity probe scan effectively monitor the gas content of gas migration. Abstract: Gas leakage can cause serious safety risks to offshore engineering facilities and offshore engineering projects. Monitoring the migration of gas in sediments is of great significance to the safety of marine engineering. In this study, we analysed the ability of ring-electrode resistivity probes (REPs) and circular point-electrode resistivity probes (CPEPs) to monitor the migration, accumulation, and release of gas in multilayered sediments (when the particle size of the overlying soil is smaller) using two groups of gas injection experiments with different gas injection pressures. In addition, the ability of REPs to monitor lateral gas migration was analysed by numerical simulations. The experimental results show that the two probes have different monitoring capabilities for different gas migration stages in multilayered sediments. REPs can effectively reflect the different stages of gas migration within the monitoring range according to the variation characteristics of the monitoring results, and they can effectively monitor the pattern, direction, and rate of gas migration. CPEPs are more sensitive, that is, the range of their monitoring results is about 10 times that of the REPs. They can accurately estimate the changes in the gas saturation of the soil around the probe.